Diskursus Pemikiran Fikih Lingkungan Ali Yafie dan Mujiono Abdillah - Rifqiya Hidayatul Mufidah (UIN Sunan Kalijaga Yogyakarta, 2016)
The results of the study, showed that Ali Yafie believes that environmental conservation is a social obligation. Has a sense for the completion of the problems of the environment, the preservation must be implemented by every element of society without aborting other groups although there are already one of the implement. Similarly, analysis of birth control that is where he is as kemadaratan wasilah to prevent the environmental, as well as a social obligation to do all of society for environmental damage caused by population growth continue. Abdillah Mujiono disagree that protecting the environment is an individual obligation which gave rise to ecological merit and sin for any mukallaf. Between the two there is a common thread theory that the juristic environment built for the need to provide environmental awareness of religious approach derived from the Quran and Hadith to achieve the benefit of the environment.